Preformulation studies of EFdA, a novel nucleoside reverse transcriptase inhibitor for HIV prevention. (August 2014) - Zhang, Wei; Parniak, Michael A.; Mitsuya, Hiroaki; Sarafianos, Stefan G.; Graebing, Phillip W.; Rohan, Lisa C.
Abstract 4′-Ethynyl-2-fluoro-2′-deoxyadenosine (EFdA) is a novel nucleoside analog of great interest because of its superior activity against wild-type and multidrug-resistant HIV-1 strains, and favorable safety profiles in vitro and in vivo. The aim of this work was to provide preformulation information of EFdA important for delivery system development. A simple, accurate and specific reverse-phase high performance liquid chromatographic (RP-HPLC) method with UV detection was developed for quantification of EFdA. In addition, physicochemical characterizations including pH solubility profile, octanol/water partition coefficient (Log Po/w), DSC analysis, field emission scanning electron microscopy, and stability studies under various conditions were conducted. EFdA existed in planar or flake shape, with a melting point of ∼130 °C, and had a pH dependent solubility. The log Po/w value of EFdA was −1.19. The compound was stable upon exposure to pH levels from 3 to 9 and showed good stability at elevated temperature (65 °C). In vitro cytotoxicity assessments were performed in two different epithelial cell lines. In cell-based studies, the EFdA selectivity index (50% cytotoxic concentration [CC50] values/50% effective concentration [EC50]) was found to be greater than 1 × 103. Permeability studies using cell- and tissue-based models showed that EFdA had an apparent permeability coefficient (Papp) < 1×10−6 cm/s and that the paracelluar pathway was the dominant transport route for EFdA. Overall, EFdA possesses favorable characteristics for further formulation development.